IMPLEMENTASI PEMBELAJARAN BILINGUAL DI TAMAN KANAK-KANAK CAHAYA MENTARI PONTIANAK KOTA - Rita Astika; Aloysius Mering; Lukmanulhakim Lukmanulhakim (Universitas Tanjungpura, 2019)
AbstractSunshine kindergarten which located in Pontianak kota is a bilingual school with English and Mandarin language, and Indonesia as the language’s instruction. The researcher is interested to conduct a research about the implementation of language learning teaching method in Sunshine kindergarten, especially in introducing English and Mandarin language. This research used descriptive methods. Data collection techniques used direct observation concerning to learning process in Sunshine, doing interview with teacher, principals and documentation. The result of the research was the school’s regulation obliges that all teacher actively use English or Mandarin in introducing the language as the curriculum of bilingual learning. The implementation of bilingual learning runs regularly because the teacher has prepared a lesson plan before teaching. Evaluation of bilingual learning to children was rarely done by teacher, it is being done once a month by testing students one by one related to the lesson given a month before. Meanwhile, it could not really run well because of some inhibiting factors, such as, there are some students who do not understand what is said by teacher and some children who experience language disorders. Then, the supporting factors are family environmental which also stimulate the development of foreign language at home. Key words: Implementation of Bilingual Learning, Learning English, Learning Chinese